Brain abscess complicating ischemic embolic stroke in a patient with cardiac papillary fibroelastoma – Case report and literature review. (August 2019) - Boukobza, Monique; Nahmani, Sarah; Deschamps, Lydia; Laissy, Jean-Pierre
Highlights: Abscess complicating a cerebral infarct is a rare entity. These abscesses do not manifest by additional neurologic deficits. In most cases a concomitant infection cannot be individualized. A cardiac papillary fibroelastoma (PFE) is a rare cardiac source of embolic stroke. Fever in patients with cerebral infarct: brain imaging follow-up is required. Abstract: A 72-year-old man without obvious risk factors initially presented with acute ischemic stroke and fever, without concomitant infection. Broad spectrum antibiotic therapy was initiated. Transthoracic and Transesophageal echocardiography, and cardiac MRI revealed a 20 mm round mass attached to the anterior mitral valve leaflet, suggesting the diagnosis of a benign cardiac tumor or a vegetation. At the site of infarction an abscess of 11 mm in diameter developed 30 days later. The patient underwent surgical valve repair for the prevention of further embolic complications. Histology revealed a cardiac papillary fibroelastoma (PFE). He made complete clinical recovery. Secondary abscess formation after ischemic stroke is rare: 11 other cases have been reported . Because they develop at the site of a previous ischemic infarct, these abscesses usually do not manifest by additional neurologic deficits, making difficult their diagnosis. In most cases a concomitant infection cannot be individualized. Even if these abscesses are a rare entity, patients with cerebral infarct presenting with fever must be closely follow-up with cerebral imaging. Even if PFE is a rare cardiac source of embolic stroke, it should be considered in the differential diagnosis of stroke in a patient where an alternative etiology has not been established.